2017
DOI: 10.4236/ojopm.2017.71001
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Oligomer from Recycled PET and Evaluated as a Corrosion Inhibitor for C-Steel Material in 0.1 M HCl

Abstract: Polyethylene terephthalate waste (PET) was depolymerized by thiodiglycol into thioglycolyzed product. The product was characterized by FTIR and 1 HNMR spectroscopy and the thermal properties (TGA, DTA) showed that the prepared compound was thermally stable until 250˚C. The efficiency of the prepared corrosion inhibitor for carbon steel was measured by using acid media (0.1 HCl) as corrosive environment and the inhibitor concentration was (0, 10, 20, 30, 40 and 50 ppm). The electrochemical technique used Tafel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The solvent thiodiglycol in combination with zinc acetate gave bis (2-(2-hydroxyethyl thio-ethyl terephthalate)) as a product. 61 Metal oxides like ZnO, Co 3 O 4 , Mn 3 O 4 , and mixed metal oxides like ZnMn 2 O 4 , CoMn 2 O 4 , and ZnCo 2 O 4 were also employed as catalysts for the depolymerisation of PET plastics. 14,62 Among these, it is remarkable to mention that the monomer BHET can be obtained in up to 70% yield when using zinc acetate and EG as solvent.…”
Section: (Bio)-chemical Recycling Of Polyestersmentioning
confidence: 99%
“…The solvent thiodiglycol in combination with zinc acetate gave bis (2-(2-hydroxyethyl thio-ethyl terephthalate)) as a product. 61 Metal oxides like ZnO, Co 3 O 4 , Mn 3 O 4 , and mixed metal oxides like ZnMn 2 O 4 , CoMn 2 O 4 , and ZnCo 2 O 4 were also employed as catalysts for the depolymerisation of PET plastics. 14,62 Among these, it is remarkable to mention that the monomer BHET can be obtained in up to 70% yield when using zinc acetate and EG as solvent.…”
Section: (Bio)-chemical Recycling Of Polyestersmentioning
confidence: 99%
“…Temperature of the reaction mixture was between 160-180 o C for 12 h, then the reaction mixture was kept at 140 o C for 3 h, then allowed to cool to room temperature. With vigorous agitation distilled water in excess to the reaction mixture to allow the black liquid viscous compound oligomer of Bis(2-((2hydroxyethyl) thio)ethyl terephthalate (BHET) to precipitate (14) . In a three neck round bottom (250 ml) attached with mechanical stirrer and thermometer (5.7gm) of (BHET) compound was added and heated for (15 min.)…”
Section: Corrosion Inhibition Measurementsmentioning
confidence: 99%
“…The temperature effect of polymeric CIs has been analyzed by different authors such as Alaoui et al [ 21 ], who suggested that the IE behavior with respect to the medium temperature is associated with the adsorption type change that presents a polymer; in this way, the increase in the IE is related to a chemisorption process that is favored by a temperature increase. In contrast, Gowraraju et al [ 23 ], Charitha et al [ 24 ] and Yasir et al [ 25 ] observed that an IE decrease as the temperature increases can be explained by a fast adsorption-desorption process and by the decomposition and/or reordering of inhibiting molecules led by a prevailing physisorption process. An implicit variable in the temperature effect on corrosion inhibition processes is the activation energy ( E a ).…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 shows some studies performed with polymeric CIs and their behavior as a function of temperature. Different types of polymers have been evaluated as CIs at different temperatures: PILs [ 19 , 20 ], synthetic polymers [ 21 ], biomacromolecules [ 22 ], carbohydrates [ 23 , 24 ], recycled PET oligomers [ 25 ] and triblock copolymers [ 26 , 27 ]. The temperature effect of polymeric CIs has been analyzed by different authors such as Alaoui et al [ 21 ], who suggested that the IE behavior with respect to the medium temperature is associated with the adsorption type change that presents a polymer; in this way, the increase in the IE is related to a chemisorption process that is favored by a temperature increase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation